STANDARD OPERATING PROCEDURE OF PANCHATIKTA GHRITA AND STUDY OF ITS ANTIMICROBIAL ACTIVITY - Manish S, *Bhoyar; Shraddha, Panchabhai; Rajeshwari, Ahirrao (International Journal of Ayurveda and Pharma Research, 2017)
Sneha kalpana is the specialized pharmaceutical procedure to prepare oleaginous medicine from Kalka and Drava- dravya. While reviewing ancient texts variations are found regarding preparatory procedures, ingredients used, confirmatory tests advised, indication of Panchatikta Ghrita. All the information available is in scattered form in different texts. To overcome these ambiguities it is necessary to develop Standard Operating Procedure (SOP). In this SOP the Sequential, Scientific and Logical illustration and documentation of each and every step is given. In Pre-Operative phase Shodhana of Guggulu and Murchchana of Ghrita was carried out. In operative phase Kwath-4L, Kalka-90gm, Guggul-70gm, Murchchit ghrita-240ml were taken together and subjected Snehasadhan vidhi for 3 days giving 2 hours of heat daily keeping the temp. in between 500 to 900 C till Snehasiddhi lakshana obtained.175gm of Panchatikta ghrita was prepared according to this SOP. It took 9 days to complete entire procedure. Quality parameter assessment was done by carrying physicochemical analysis viz. Sp. Gravity, Ref. index, Congealing point Sap value, Iodine value etc. Further antimicrobial study of Panchatikta ghrita against E-coli, Streptococcus Pyogens, Staphylococcus Aurens, S.typhi, C. Albicans etc was carried out. But no zone of inhibition was seen for any of the selected micro-organisms. The in vitro negative results didnt entirely reveal its therapeutic efficacy. In Ayurvedic therapeutics the Pharmacokinetics and Pharmacodynamics of the drug entirely depends upon Rasa, Veerya, Veepaka, Prabhava and balance of Tridosha in the body. The ingredients of Panchatikta Ghrita with their Rasa, Veerya, Veepak are very much competent to exhibit antimicrobial property from Ayurvedic perspective.